2011
DOI: 10.1590/s1678-77572011000200007
|View full text |Cite
|
Sign up to set email alerts
|

Craniofacial characteristics of Caucasian and Afro-Caucasian Brazilian subjects with normal occlusion

Abstract: ObjectiveThe objective of this study was to compare the skeletal, dental and soft tissue characteristics of Caucasian and Afro-Caucasian Brazilian subjects with normal occlusion and to evaluate sexual dimorphism within the groups.Material and MethodsThe sample comprised lateral cephalograms of untreated normal occlusion subjects, divided into 2 groups. Group 1 included 40 Caucasian subjects (20 of each sex), with a mean age of 13.02 years; group 2 included 40 Afro-Caucasian subjects (20 of each sex), with a me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 20 publications
3
10
0
2
Order By: Relevance
“…The value found in the relationship of the maxilla with the base of the skull (SNA) showed similarity to the results found by Silva 9 13 found higher values in the male gender than those found in the present study, whereas Janson et al 21 found lower values for both genders, since in his study no statistically significant difference was found for the male and female genders.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The value found in the relationship of the maxilla with the base of the skull (SNA) showed similarity to the results found by Silva 9 13 found higher values in the male gender than those found in the present study, whereas Janson et al 21 found lower values for both genders, since in his study no statistically significant difference was found for the male and female genders.…”
Section: Discussionsupporting
confidence: 90%
“…However, there was evident need to know the alterations in the linear and angular measurements of the dento-skeletal structures during growth, in addition to establishing their values in the different ethnic groups [9][10][11][12][13][14][15] . In Individuals of Afro-Brazilian descent there are few studies that have been concerned with the cephalometric evaluation of this ethnic group in Brazil, with the outstanding studies being those of Silva 9 18 , Magnani et al 19 , de Freitas et al 20 , Janson et al 21 , Sobreira et al 22 and Carvalho et al 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Different soft tissue behavior may be attributed to several factors: soft tissue thickness, [22][23][24][25] pretreatment labial tension, 25,26 face height, 27 variations in the amount of adipose or muscle tissue present in the lips, area of lip-tooth contact, lip length, 28 and different ethnicities. 29 Previous studies have not reported the long-term soft tissue changes following the treatment of adult anterior open bite using skeletal anchorage. At the end of 4 years posttreatment, a statistically significant relapse was noted in the forward movement of the upper lip and upper lip sulcus, backward movement of the soft tissue pogonion, increase of the soft tissue facial height, and a reduction in the SN 0 B 0 angle (Table 6).…”
Section: Discussionmentioning
confidence: 99%
“…Even though cephalometric values are still used as a normality reference in orthodontics, it is known that variability can occur from each patient, for many different reasons. Innumerous studies have shown that cephalometric numbers differ according to race, genetics backgrounds or orofacial anomalies …”
Section: Introductionmentioning
confidence: 99%